Analisis Kinerja dan Jumlah Armada Terhadap Demand Penumpang Kereta Commuter Indonesia Lintas Manggarai-Bogor - Leliana, Arinda; Oktaviastuti, Blima; Sa'dillah, M (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2020)
The main factor of congestion is because the number of private vehicles isn't comparable to its infrastructure. The railroad system is one of the transportation modes having a characteristic and excellence for carrying people or things, saving space so we can decrease a jam. With that characteristic and excellence, the role of the railroad system needs to be an improvement. To developing need to have a performance observation for knowing is Indonesian commuter train has good enough performance or no. Furthermore, the forecast of a growing passenger which is the railroad services has been doing for getting an increasing passenger level, so that it can determine the production growth of the fleet, in the case of fulfilling the requests of Indonesia commuter customers in the future. This study uses a quantitative research design with descriptive research types. In the research are using primer data and secondary data. The next analysis process is to analyze the level of passengers and the number of facilities needed. Aside from that, the author has used math formulas. The results obtained by the travel time on the Manggarai-Bogor route obtained 73 minutes. The number of passengers in 2024 is estimated at 182,647,716 passengers with 500,405 passengers per day with a traffic capacity of 501,696.